Unravelling the Ukrainian Revolution: “Dignity,” “Fairness,” “Heterarchy,” and the Challenge to Modernity - Wynnyckyj, Mychailo (Kyiv-Mohyla Humanities Journal, 2020)
Ukraine’s “Revolution of Dignity,” spanning both the 2013–2014 protests in Kyiv’s city center and the mass mobilization of grass-roots resistance against Russian aggression in 2014–2015 and thereafter, manifest new interpretations of ideas and philosophical concepts. In the first part of the article we unravel the meaning of the Ukrainian word hidnist (roughly translated as “dignity”) – a moniker of the revolution whose significance remains underestimated. In the second part we situate Ukraine’s revolution within a broader context of “modernity” and suggest its individualist foundation may be replaced by a form of “personalism” – an ethic that echoes that of Ukraine’s revolutionaries. In the third part of the article, we delve into the substance of the revolution’s agenda: its protagonists’ promise to build a non-hierarchical community of “fairness” (spravedlyvist). In the fourth and final section, the main argument of the article is summarized, namely: that the shift from individualism to personalism in social interaction and the transition from hierarchy to heterarchy in power relations, particularly with respect to institutionalizing “fairness,” embodied in the various structures and organizations formed during Ukraine’s Revolution of Dignity, may have been reflective of more comprehensive trends in ideational change affecting European (Western) civilization.